PENDEKATAN INTEGRATIF-INTERKONEKTIF: TINJAUAN PARADIGMATIK DAN IMPLEMENTATIF DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muslih Hidayat (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
Islam is a religion, based on god revelation is no doubt inside. Every Muslim realizes this truth. In the other hand, Islam is not only dichotomist religion but also science which could not be separated from the knowledge and technology improvement nowadays. The focus of Islam is on Islamic science. At the previous decades, there was sciences dichotomy between Islamic science and general science such as physics, social, humanist, and so on. That reality is happened on some Islamic institution as Islamic science learning administration and improvement practitioners. An unacceptable condition will be arise if this dichotomy problem is not solved by the stakeholders.This study is focus on paradigm and implementation approach of integration-interconnection in Islamic religion education learning.